ABOUT THE NEED AND BENEFITS OF THE RESEARCH OF BOOK SCIENCE HISTORY: AN ATTEMPT OF ANALYSIS FROM THE PERSPECTIVE OF THE SCIENCE OF SCIENCE - MIGOŃ, KRZYSTOF (Knygotyra, 2013)
Among historical sciences, the history of science is nowadays of particular importance. In parallel to the general history of science, considered autonomous or as part of the science of science, studies on the history of individual scientific disciplines are fast developing. Their significance is not limited to the pure knowledge. In fact, understanding the evolution of a given discipline is an indispensable component in contemporary research and relevant to practical applications. The book science history has become a separate specialty within bibliological research since the mid-20th century. In the following years, various approaches to the subject matter and means of presentation of historical data have gradually developed. In the voluminous multilingual literature one can see the domination of case studies, these being mostly biographic (‘bibliology classics’), institutional, and topical. In contrast, there is a relative paucity of synthetic studies aimed at generalizations at national (countrywide) and global levels. This paper offers a review of the most important research problems related to the history of bibliology, with a particular emphasis on Central and Eastern European countries. It includes the proposal of a model construction and content of a future synthetic treatise ‘The history of world bibliology’. Such a monumental work should address the following issues: the state-ofthe-art of the ‘book world’ as the basis of the development of bibliological thought, the position of bibliology among other sciences, approaches and views about the subject and scope of book science, cognitive competences of book science, its notional instrumentation and terminology, central research categories, schools in bibliology, relationships among scientists, institutions and organization of science, sources of bibliological knowledge and research methods, the system and typology of book science literature.